The nnexus between executive compensation and firm performance: Does governance and inequality matter? - Tapiwa Muzata; Godfrey Marozva (Global Business & Finance Review (GBFR), 2023)
Purpose: The main aim of this study is to empirically investigate the relationship between executive compensation, inequality, and corporate governance, thus filling a gap in extant literature. Design/methodology/approach: The methodology used calculated the salary Gini (s-Gini) and governance indices (G-index) for companies in the sample and these were used as proxies for inequality and corporate governance respectively. The dataset is panel in nature. It comprises 46 conveniently selected largest JSE listed companies (by market capitalisation). A 2-step system GMM was used to determine if s-Gini and G-index were channels through which executive compensation could influence company performance. While considering a dynamic specification, the GMM estimator addressed possible endogeneity bias. GMM estimation method addressed potential over or underestimation of the relationship between company performance and executive compensation because it was considered more efficient on shorter panels. GMM analysis on companies listed on the JSE Top40 index was from 2008 to 2020. Overall, the methodology and analysis employed provide valuable insights into the complexities between executive compensation, inequality, corporate governance, and company performance, shedding light on important factors that can influence company's performance. Findings: Results indicated that as executive compensation improved, company performance deteriorated. Furthermore, varied impact of inequality on performance measures were recorded. The observation was that inequality influenced performance in diverse ways. This accentuated the convoluted nature of this relationship. The study also established that both inequality and corporate governance are channels through which executive remuneration affects performance. Additionally, a positive nexus between governance and net profit margin was discovered. Research limitations/implications: The results imply that: higher executive pay does not always yield better company performance; the effects of executive pay on performance are mediated by the level of inequality within the company and the quality of corporate governance practices; good corporate governance practices can enhance financial performance. It is recommended that companies should prioritise espousal of sound corporate governance practices because they have positive influence on performance. Moreover, diligent attention must be given to how executive compensation is configured. Poorly designed compensation packages erode company value. Conversely, properly structured ones may enhance performance and successively improve company value. This study is focused solely on the Top40 largest listed companies in South Africa. The findings may not be generalisable to all listed entities, as there could be variations in the relationship between executive compensation, inequality, and corporate governance across companies of different sizes. By concentrating on the largest entities, the study may gloss over nuances that exist in smaller companies. However, it is important to state that the insights gained from this research are still valuable and can provide useful guidance to policymakers, shareholders, and other stakeholders in understanding the interaction of the variables examined within the context of larger firms. Future research should consider expanding the sample to include a broader range of listed entities to obtain a more comprehensive understanding of these relationships across the entire corporate landscape. Originality/value: This study contributes to research gap h ighlighted by Core e t al. (1 999), Morais et al. (201 3) and Enderle (2018) regarding the limited literature on income inequality within companies and strategies to mitigate such disparities. By incorporating income inequality as a key factor rarely explored in dialogues on executive compensation and performance, we contribute to knowledge in this field. Furthermore, the study sheds light on the interplay between executive compensation, corporate governance, and inequality as catalysts that influence company performance. To progress the discourse, future studies should investigate this phenomenon within the context of a pandemic, providing valuable insights to enhance the resilience of companies.
Keywords: 650; Executive compensation; Company performance; Inequality; Governance; JSE